Empathic responsiveness in amygdala and anterior cingulate cortex in youths with psychopathic traits. (12th March 2013) - Marsh, Abigail A.; Finger, Elizabeth C.; Fowler, Katherine A.; Adalio, Christopher J.; Jurkowitz, Ilana T. N.; Schechter, Julia C.; Pine, Daniel S.; Decety, Jean; Blair, R. J. R.
Abstract : Background: Psychopathic traits are associated with increases in antisocial behaviors such as aggression and are characterized by reduced empathy for others' distress. This suggests that psychopathic traits may also impair empathic pain sensitivity. However, whether psychopathic traits affect responses to the pain of others versus the self has not been previously assessed. Method: We used whole‐brain functional magnetic resonance imaging to measure neural activation in 14 adolescents with oppositional defiant disorder or conduct disorder and psychopathic traits, as well as 21 healthy controls matched on age, gender, and intelligence. Activation in structures associated with empathic pain perception was assessed as adolescents viewed photographs of pain‐inducing injuries. Adolescents imagined either that the body in each photograph was their own or that it belonged to another person. Behavioral and neuroimaging data were analyzed using random‐effects analysis of variance. Results: Youths with psychopathic traits showed reduced activity within regions associated with empathic pain as the depicted pain increased. These regions included rostral anterior cingulate cortex, ventral striatum (putamen), and amygdala. Reductions in amygdala activity particularly occurred when the injury was perceived as occurring to another. Empathic pain responses within both amygdala and rostral anterior cingulate cortex were negatively correlated with the severity of psychopathic traits as indexed by PCL:YV scores. Conclusions: Youths with psychopathic traits show less responsiveness in regions implicated in the affective response to another's pain as the perceived intensity of this pain increases. Moreover, this reduced responsiveness appears to predict symptom severity.